Multidrug-Resistant CTX-M-(15, 9, 2)- and KPC-2-Producing Enterobacter hormaechei and Enterobacter asburiae Isolates Possessed a Set of Acquired Heavy Metal Tolerance Genes Including a Chromosomal sil Operon (for Acquired Silver Resistance) - Andrade, Leonardo N.; Siqueira, Thiago E. S.; Martinez, Roberto; Darini, Ana Lucia C. (Frontiers in Microbiology, 2018)
Bacterial resistance to antibiotics is concern in healthcare-associated infections. On the other hand, bacterial tolerance to other antimicrobials, like heavy metals, has been neglected and underestimated in hospital pathogens. Silver has long been used as an antimicrobial agent and it seems to be an important indicator of heavy metal tolerance. To explore this perspective, we searched for the presence of acquired silver resistance genes (sil operon: silE, silS, silR, silC, silF, silB, silA, and silP) and acquired extended-spectrum cephalosporin and carbapenem resistance genes (blaCTX-M and blaKPC) in Enterobacter cloacae Complex (EcC) (n=27) and Enterobacter aerogenes (n=8) isolated from inpatients at a general hospital. Moreover, the genetic background of the silA (silver-efflux pump) and the presence of other acquired heavy metal tolerance genes, pcoD (copper-efflux pump), arsB (arsenite-efflux pump), terF (tellurite resistance protein), and merA (mercuric reductase) were also investigated. Outstandingly, 21/27 (78%) EcC isolates harbored silA gene located in the chromosome. Complete sil operon was found in 19/21 silA-positive EcC isolates. Interestingly, 8/20 (40%) E. hormaechei and 5/6 (83%) E. asburiae co-harbored silA/pcoD genes and blaCTX-M-(15, 2 or 9) and/or blaKPC-2 genes. Frequent occurrences of arsB, terF, and merA genes were detected, especially in silA/pcoD-positive, multidrug-resistant (MDR) and/or CTX-M-producing isolates. Our study showed co-presence of antibiotic and heavy metal tolerance genes in MDR EcC isolates. In our viewpoint, there are few studies regarding to bacterial heavy metal tolerance and we call attention for more investigations and discussion about this issue in different hospital pathogens.